2021
DOI: 10.1002/csc2.20541
|View full text |Cite
|
Sign up to set email alerts
|

Can optimizing seeding rate and planting density alleviate the yield loss of double‐season rice caused by prolonged seedling age?

Abstract: Prolonged seedling age (PS) caused by delayed transplanting frequently occurs in double-season rice (Oryza sativa L.), leading to a significant grain yield loss. However, it is not clear whether optimizing the seeding rate in the nursery and planting density in the field could compensate for this yield loss. Field experiments with two seedling age, two planting density, and two seeding rate treatments were conducted in the early and late growing seasons of 2013 and 2014 in Wuxue County, Hubei Province, China. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
(71 reference statements)
0
2
0
Order By: Relevance
“…Other factors affecting the number of tillers were planting distance, growing season, and the use of fertilizers. Wide planting, supported by a good environment, will increase the number of tillers (Asmamaw 2015;Huang et al 2021). The grains' length ranged from 6.42-9.86 mm (CV=12.73%), and Ale kalaha dikar has the longest grain of 9.86 mm and Hare mean 14, the shortest of 6.42 mm.…”
Section: Agro-morphological Characterizationmentioning
confidence: 99%
“…Other factors affecting the number of tillers were planting distance, growing season, and the use of fertilizers. Wide planting, supported by a good environment, will increase the number of tillers (Asmamaw 2015;Huang et al 2021). The grains' length ranged from 6.42-9.86 mm (CV=12.73%), and Ale kalaha dikar has the longest grain of 9.86 mm and Hare mean 14, the shortest of 6.42 mm.…”
Section: Agro-morphological Characterizationmentioning
confidence: 99%
“…At the same time, the adverse effects of prolonged seedling age are also worthy of attention. A long seedling period not only leads to the deterioration of seedling quality but also inhibits plant growth and yield formation after transplanting [18]. Moreover, studies have indicated that when the seedling age exceeds 40 days, it can result in premature heading, affecting the double-cropping rice yield [19].…”
Section: Introductionmentioning
confidence: 99%